Aristophanes and Plato: the poet in the polis - Pompeu, Ana Maria César (2014)
Our research has as main objective to identify in the comedies of Aristophanes the figure of the poet and his work in the city as educator of the people, establishing a dialogue between Plato’s criticism of poetry and disorders of the pólis and the institution of righteous speech by the comic poet in the aristophanic comedies. This article will deal more specifically the relationship between mimesis and Eros in the two authors. Plato uses Aristophanes in the Symposium as a comedy writer to make clear the way for Socrates, and the poet, as in comedies, often combines the ridiculous with the materialism for restorative function to return the distortions of political life to nature. In Tesmoforiantes, we witnessed a true withdrawal of Theatre Mask, a critique of the foundations of serious representation, the tragic, by to use men actors in female roles, with the ridiculous manifest by the travesty on the stage of Euripides’ relative in an old woman.